Proactive Fault Tolerance and Minimizing Task Execution Failure in A Cloud Data Center - Kandil, Ayman (2024)
A Master of Science thesis in Computer Engineering by Ayman Kandil entitled, “Proactive Fault Tolerance and Minimizing Task Execution Failure in A Cloud Data Center”, submitted in December 2024. Thesis advisor is Dr. Ra’afat Abu-Rukba and thesis co-advisor is Dr. Salam Dhou. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).